Adaptive Chirality of an Achiral Cucurbit[8]uril‐Based Supramolecular Organic Framework for Chirality Induction in Water. Issue 12 (3rd February 2021) - Li, Yawen; Li, Qingfang; Miao, Xiaran; Qin, Chunyan; Chu, Dake; Cao, Liping
Abstract: Chiral framework materials have been developed for many applications including chiral recognition, chiral separation, asymmetric catalysis, and chiroptical materials. Herein, we report that an achiral cucurbit[8]uril‐based supramolecular organic framework (SOF‐1 ) with the dynamic rotational conformation of tetraphenylethene units can exhibit adaptive chirality to produce M ‐SOF‐1 or P ‐SOF‐1 with mirror‐image circular dichroism (CD) with gabs ≈±10 −4 and circularly polarized luminescence (CPL) with glum ≈±10 −4 induced by L ‐/ D ‐phenylalanine in water, respectively. The chirality induction in CD (gabs ≈−10 −4 ) and CPL (glum ≈−10 −4 ) of P ‐SOF‐1 from achiral SOF‐1 can be presented by using a small amount of adenosine‐5′‐triphosphate disodium (ATP) or adenosine‐5′‐diphosphate disodium (ADP) (only 0.4 equiv) in water. Furthermore, the adaptive chirality of SOF‐1 can be used to determine dipeptide sequences (e.g., Phe‐Ala and Ala‐Phe) and distinguish polypeptides/proteins (e.g., somatostatin and human insulin) with characteristic CD spectra. Therefore, achiral SOF‐1 as an ideal chiroptical platform with adaptive chirality may be applied to determine the enantiopurity of amino acids (e.g., L ‐/ D ‐phenylalanine), develop aqueous CPL materials, and distinguish biological chiral macromolecules (e.g., peptides/proteins) via chirality induction in water. Abstract : An achiral supramolecular organic framework (SOF) exhibits adaptive chirality with dual circular dichroism and circularly polarized luminescence responses when meeting various chiral guests, including L ‐/ D ‐Phe, adenosine derivatives, and peptides/proteins via chirality induction in water. The adaptive chirality of the SOF can be used as a chiroptical platform to determine the enantiopurity, develop aqueous CPL materials, and distinguish peptides/proteins.